﻿Aliens eating aliens: an introduced amphipod as a potential prey of an invasive rocky shore crab in laboratory experiments - Nicolas Spilmont; Laurent Seuront (Aquatic Invasions)
Behavioural interactions between introduced predators and introduced prey are still largely underestimated. The present work takes advantage of the co-occurrence of two introduced species, the Asian shore crab Hemigrapsus sanguineus and the amphipod Ptilohyale littoralis, respectively first recorded on rocky shores along the French coast of the eastern English Channel in 2005 and 2016. In this context, the predation by male and female H. sanguineus on P. littoralis was examined under controlled laboratory conditions, by presenting either juveniles of the blue mussel Mytilus edulis or adult P. littoralis to H. sanguineus. We subsequently assessed the potential prey preference of the Asian shore crab for P. littoralis and M. edulis by presenting the two prey items simultaneously in the same proportion. In the absence of choice, male H. sanguineus preyed significantly more on M. edulis than P. littoralis. In contrast, females preyed significantly less on M. edulis than P. littoralis; however, male and female H. sanguineus consumed similar numbers of P. littoralis. When choice was possible between P. littoralis and M. edulis, the crab did not exhibit preference stricto sensu for any type of prey. These results suggest that the Asian shore crab cannot be considered as a naive predator when confronted to a newly introduced prey. Our results also suggest that the amphipod P. littoralis did not exhibit any effective antipredator response towards the crab. These observations nevertheless warrant further work on the effects of abiotic factors (e.g. temperature) as well as other biotic interactions (e.g. presence of other prey or predators for H. sanguineus) may have on the observed prey-predator interactions between H. sanguineus and M. edulis and P. littoralis.